2012
DOI: 10.1194/jlr.p020909
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin increase after fat overload is related to postprandial hypertriglyceridemia in morbidly obese patients

Abstract: Obesity is an increasingly prevalent health problem, very often accompanied by other diseases, the most common being insulin resistance, type 2 diabetes mellitus, and cardiovascular complications ( 1, 2 ). Furthermore, an association has been reported between obesity and both oxidative stress and increased infl ammation ( 3, 4 ). Obesity facilitates the development of a low-grade infl ammatory state, characterized by increased plasma levels of proinfl ammatory cytokines ( 4 ). However, the factors that trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 26 publications
11
98
0
4
Order By: Relevance
“…Mixed hyperlipidic/hyperglucidic meals (51 g lipids, 81 g carbohydrates) also increase plasma LPS in the postprandial phase in healthy lean men (Ghanim et al, 2009. Recent studies confirm these results of postprandial endotoxemia in type 2 diabetic subjects consuming 75 g of lipids (Harte et al, 2012) and in morbidly obese subjects consuming a 50 g lipid load (Clemente-Postigo et al, 2012). Among postprandial studies, some used dairy fat (butter or cream), other used mixed fatrich foods (often eggs and sausage) or simple oil load or, in the form of single food or into mixed meals, and altogether fat intake was high (Tab.…”
Section: Intestinal Lipid Absorption Contributes To the Translocationsupporting
confidence: 72%
“…Mixed hyperlipidic/hyperglucidic meals (51 g lipids, 81 g carbohydrates) also increase plasma LPS in the postprandial phase in healthy lean men (Ghanim et al, 2009. Recent studies confirm these results of postprandial endotoxemia in type 2 diabetic subjects consuming 75 g of lipids (Harte et al, 2012) and in morbidly obese subjects consuming a 50 g lipid load (Clemente-Postigo et al, 2012). Among postprandial studies, some used dairy fat (butter or cream), other used mixed fatrich foods (often eggs and sausage) or simple oil load or, in the form of single food or into mixed meals, and altogether fat intake was high (Tab.…”
Section: Intestinal Lipid Absorption Contributes To the Translocationsupporting
confidence: 72%
“…In the present study, these indices were similar between subjects with slightly different phenotypes, especially regarding the insulin resistance markers. Contradictory results regarding the association of these indices with LPS concentration have been reported previously [21,37]. We showed that sagittal abdominal diameter, an unusual indicator of abdominal obesity, distinguished subjects with different concentrations of plasma LPS.…”
Section: Discussionsupporting
confidence: 55%
“…In another study mice plasma were not diluted, endotoxemia was around 0.8 EU/mL (Lonza endpoint kit) but no information on the preparation was provided [28]. The same is observed in humans: only some authors described their procedure to prepare sample, and a study led by Clemente-Postigo et al [29] did not dilute human plasma with a Lonza kit contrary to Erridge et al [30] which diluted the samples at 1/10 (as us) with a Cambrex kit. However in these 2 studies endotoxemia values were around 0.8 EU/mL like in our experiments using a Cape Cod kit.…”
Section: Discussionmentioning
confidence: 89%